2006
DOI: 10.1111/j.1574-695x.2006.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the ability of oral streptococci to interact with platelet glycoprotein Ibα and with the salivary low-molecular-weight mucin, MG2

Abstract: The oral streptococci Streptococcus sanguinis, Streptococcus gordonii and Streptococcus oralis are common aetiological agents of infective endocarditis, and their ability to adhere to and induce the aggregation of platelets is thought to be a virulence trait. The platelet glycoprotein GPIbalpha has been implicated as the adhesion receptor for S. sanguinis and S. gordonii, but it is not known if this is the case for S. oralis and other species. The aim of this study was to determine the GPIbalpha-interactive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 31 publications
(44 reference statements)
1
27
0
Order By: Relevance
“…The wide distribution of these carbohydrates suggests that this adherence mechanism mediates binding to these carbohydrates in a range of contexts and, as a result, is likely important in adherence to not only platelets and endothelial cells but also other host surfaces, including the oral cavity. Previous studies have demonstrated a reduction in binding of other SRRP mutants to salivary proteins and in vitro models of oral surfaces (41,(62)(63)(64). The demonstration that a fap1 mutant has reduced adherence for an oral epithelial cell line supports the hypothesis that this protein contributes to S. oralis binding in the oral cavity; however, further studies will be required to determine the precise contribution.…”
Section: Discussionmentioning
confidence: 67%
“…The wide distribution of these carbohydrates suggests that this adherence mechanism mediates binding to these carbohydrates in a range of contexts and, as a result, is likely important in adherence to not only platelets and endothelial cells but also other host surfaces, including the oral cavity. Previous studies have demonstrated a reduction in binding of other SRRP mutants to salivary proteins and in vitro models of oral surfaces (41,(62)(63)(64). The demonstration that a fap1 mutant has reduced adherence for an oral epithelial cell line supports the hypothesis that this protein contributes to S. oralis binding in the oral cavity; however, further studies will be required to determine the precise contribution.…”
Section: Discussionmentioning
confidence: 67%
“…Crittenden cups and a custom-made silicone impression device, respectively (Plummer et al 2006). Whole stimulated saliva was collected from several volunteers by chewing sugarfree gum and unstimulated saliva was collected over several minutes by allowing saliva to pool briefly in the mouth.…”
Section: Saliva Collection and Western Blottingmentioning
confidence: 99%
“…By elucidating the salivary receptor(s) in this competition phenomenon, we will determine whether Hsa-mediated attachment of S. gordonii directly blocks the same receptor utilized by S. sanguinis or prevents access of S. sanguinis to its own pellicle receptor(s). For example, both S. gordonii and S. sanguinis have been shown to bind salivary mucin MG2 (35,52). Alternatively, salivary pellicle binding sites identified for S. sanguinis include a complex of ␣-amylase and the light chain of sIgA (7).…”
Section: Discussionmentioning
confidence: 99%